Fitase na digestibilidade de alimentos proteicos vegetais para o jundiá Rhamdia voulezi - Fries, Edionei Maico (2014)
This study had determined the effect of the supplementation of phytase (1,500 IU kg-1 diet phytase) on apparent digestibility, minerals availability, mineral deposition in the bones, intestinal histology and proximate analysis for catfish fillets (Rhamdia voulezi). Were utilized 360 catfishes with average weight of 236.98±54.02 g and average length of 27.39±2.02 cm distributed in 24 tapered conical tanks of 500L each for the excreta collection were used. The experimental design was completely randomized with eight treatments and three replications. Were measured three protein foods (soybean meal, canola and sunflower) and the treatments consisted in the formulation of two diets references with about 30% crude protein and 4,240 kcal of gross energy kg-1 and two test diets for each tested feed. For this, after the mixing of the ingredients were added 1,500 IU of phytase kg-1 in a repetition of each diet, obtaining four diets without phytase supplementation and four diets with enzyme supplementation. The experimental diets were composed of 30% of the test ingredient and 70% of the reference diet and chromium oxide (Cr2O3) was used as an inert tracer in a proportion of 0.2%. Data were tabulated and submitted to analysis of variance and later was performed the multiple comparison test of Tukey (p<0.05). Factor analysis for the coefficients of apparent digestibility showed effect (p<0.05) for the interaction between ingredients and supplementation or not of phytase, with soybean meal showing the highest apparent digestibility values for dry matter, protein and ether extract. The availability of nutrients from food had effect (p<0.05) for food and supplementation of phytase enzyme, with the best results observed for fish fed with the diet supplemented with the enzyme phytase. The enzyme supplementation improves the availability of calcium and magnesium being the best values for the availability founded on the soybean meal. The villus height and thickness of the intestinal muscle layer and the chemical composition had varied (p<0.05) in accordance with treatments and with ingredients. The major intestinal villus height was observed in the reference diet with enzyme and lager thickness of the muscular layer for diet without phytase canola meal. There were not observed differences (p>0.05) with or without phytase on phosphorus retention. Moreover, all ingredients with or without supplementation of phytase showed differences (p<0.05) on the magnesium deposition in bones. Was observed that the protein ingredients of vegetable origin evaluated have responded on the different way the effect of phytase. Among the evaluated ingredients, soybean meal had showed the best digestibility coefficients and the supplementation of phytase had improved the availability of the minerals calcium and magnesium for the fish analyzed.